Ethno-psychopharmacology : advances in current practice - Ng, Chee H.; Lin, Keh-Ming; Singh, Bruce S.; Chiu, Edmond Y. K. (Cambridge : Cambridge University Press, 2012)
No one reacts or responds to a drug in exactly the same way, just as no two persons are exactly alike. Individual and ethnic differences in drug response have been consistently found in clinical practice. This book covers all the important factors that explain how and why drug treatments used in psychiatry affect individuals and ethnic groups differently. It will increase understanding of how biological differences interact with social, cultural and environmental factors to bring about overall effects of medications, particularly in individuals from various ethnicities. This book uniquely brings these varied aspects together to consider a holistic approach to drug therapy across diverse biological make-up and cultures. This information has direct practical use in the clinical setting. -- Provided by publisher.
Foreword Mario Maj; Acknowledgements; Contributors; 1. Introduction Isaac Schweitzer; 2. Culture and psychopathology Juan Mezzich, M. Angeles Ruiperez and Helena Villa; 3. Culture and ethnicity in psychopharmacotherapy Keh-Ming Lin, Chia-Hui Chen, Shu-Han Yu and Sheng-Chang Wang; 4. Ethnic differences in psychotropic drug response and pharmacokinetics Timothy Lambert, Trevor Norman 5. Pharmacogenetics of ethnic populations Min-Soo Lee, Rhee-Hun Kang and Sang-Woo Hahn; 6. Variation in psychotropic responses in the Chinese populatio Tian-Mei Si; 7. Variations in psychotropic response in the Hispanic population Deborah L. Flores and Ricardo Mendoza; 8. Identifying interethnic variations i psychotropic response in African-Americans and other ethnic minorities William B. Lawson; 9. Complementary medicines in mental disorders Xin Yu; 10. Cultural factors and the use of psychotropic medications Chee H. Ng and Steven Klimidis 11. Outpatient prescribing practices in Asian countries Pichet Udomratn and Chee H. Ng; 12. Psychiatric inpatient psychotropic prescribing in East Asia Chay-Hoon Tan; 13. Pharmaco-economic implications for Asia and other economically disadvantaged countries Norman Sartorius; 14. Integrating theory, practice and economics in psychopharmacology Keh-Ming Lin, Chun-Yu Chen, Chia-Hui Chen, Jur-Shan Cheng and Sheng-Chang Wang; 15. Research directions in ethno-psychopharmacology Chee H. Ng; Index.
Originally published: 2008.
Includes bibliographical references and index.
Keywords: Ethnopharmacology; Psychopharmacology; Ethnopsychology; Ethnopharmacology; Ethnopsychology; Psychopharmacology